Análise proteômica diferencial em raízes de plântulas de arroz (Oryza sativa L.) submetidas ao estresse por ferro - Ahlert, Renata Juliana (2010)
Rice crop has great food and economic importance. Iron is an essential element for the development of crop and necessary for essential plants functions, such as photosynthesis, respiration and DNA synthesis. However, under irrigated cultivation conditions, the low redox potential leads to reduction of iron in the soil solution which is readily available and can become toxic to plants if absorbed in excess. In rice production areas of Rio Grande do Sul, the iron has caused problems toxicity and the use of tolerant cultivars becomes an important strategy to solve the problem being necessary the study of mechanisms that give this tolerance to plants application in breeding programs. Proteomics is an important tool, which through combination of techniques such as two-dimensional gel electrophoresis and mass spectrometry allows the analysis of proteins complex involved in response to adverse environmental conditions. The objective of this study was to analyze and identify proteins with differential expression in roots of rice cultivars exposed to iron stress, to identify mechanisms involved in stress tolerance. It was used two rice cultivars, Epagri 107 and BR-IRGA 410, tolerant and sensitive to the iron toxicity, respectively, which were subjected to treatment with 7mM FeSO4EDTA. Through two-dimensional electrophoresis, it was identified 284 spots with differential expression between combinations of treatment (between cultivars and plants treated and control). Of this total, 93 proteins were identified by mass spectrometry. The identified proteins were involved in carbohydrate metabolism, signal transduction, related to plant defense, transcription factors, transposons, nucleic acids, redox reactions, among other functions. Many of the proteins have no known function. The glutathione Stransferase protein and GATA type transcription factor that have direct relation to iron metabolism were differentially expressed in the tolerant cultivar when submitted to stress. Its association with the tolerance mechanism requires, however, be confirmed.